emPAI‐assisted strategy enhances screening and assessment of Mycobacterium tuberculosis infection serological markers - Ma, Guorong; Wang, Pei; Yang, Yanhui; Wang, Wei; Ma, Jinhua; Zhou, Lin; Ouyang, Junlin; Li, Rongxiu; Zhang, Shulin (Microbial biotechnology, 2021)
Summary Discovering new serological markers of Mycobacterium tuberculosis (MTB) infection and establishing a rapid and efficient detection technology is of great significance for the prevention and control of tuberculosis. In this study, we established an exponentially modified protein abundance index (emPAI) value‐assisted strategy to investigate and improve the screening efficiency of serological biomarkers of tuberculosis. First, we used LC‐MS/MS to analyse MTB culture filtrate proteins (MTB‐CFPs), and 632 MTB proteins were identified. Then, the characteristic values of MTB‐CFPs – including emPAI value, molecular weight (Mw), isoelectric point (pI), grand average of hydropathy (GRAVY), transmembrane domain (TMD) and functional groups were calculated. Next, we successfully prepared 10 MTB proteins with emPAI value > 1.0 and recombinantly expressed these proteins in Escherichia coli. At the same time, 3 MTB proteins with emPAI between 0.1 and 0.5 were randomly selected as the control groups, and the immunogenicity of the recombinant MTB proteins was detected using ELISA. The sensitivity and receiver operating characteristic (ROC) curves were calculated for each recombinant MTB protein. The results showed that the areas under the curve (AUC) value of Rv2031c, Rv0577, Rv0831c, Rv0934 and Rv3248c were all higher than those of Rv3875 (AUC, 0.6643). Further analysis of the relationship between emPAI value and antibody sensitivity, AUC value and antibody affinity in mice immunized with recombinant MTB protein showed that emPAI values were positively correlated with them, and R‐squared value ranged from 0.64 to 0.79. The only exception was ESAT‐6 (encoded by the Rv3875 gene), which AUC value was relatively low owing to its strong immunosuppressive properties. This study provides a rationale for the serological marker screening of emPAI‐assisted tuberculosis clinical test. The results also provide new technical support for the screening of candidate serological markers of infectious diseases in the future. The areas under the curve (AUC) value of Rv2031c, Rv0577, Rv0831c, Rv0934, and Rv3248c were all higher than those of Rv3875 (AUC, 0.6643). Further analysis of the relationship between emPAI value and antibody sensitivity, AUC value, and antibody affinity in mice immunized with recombinant MTB‐protein showed that emPAI values were positively correlated with them, and R squared value ranged from 0.64 to 0.79. This study provides a rationale for the serological marker screening of emPAI‐assisted tuberculosis clinical test. The results also provide new technical support for the screening of candidate serological markers of infectious diseases in the future.